2019
DOI: 10.4018/ijcbpl.2019100103
|View full text |Cite
|
Sign up to set email alerts
|

Do They Truly Intend to Harm Their Friends?

Abstract: This present study probes and reveals the student's motives in their online interactive communication which can be considered as a cyberbullying act. The data is collected from 157 blog archives and interview sessions with 12 selected students. These students were selected purposively from Universitas Lancang Kuning, Indonesia, due to their high frequency of producing comments in their blogs which are cyberbullying in nature. From a total of 6,259 comments, this study focused on 255 that indicates online aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
(3 reference statements)
2
3
0
Order By: Relevance
“…The high percentage of bullying accident done by the students in SMP Muhammadiyah Kudus does not mean hurt the friends physically and psychotically, but they only want to have fun with their friends. This finding is in line with Hamuddin, B etc (2019), that some students do bullying in order to have fun and make a joke with their friends.…”
Section: Findings and Discussionsupporting
confidence: 90%
“…The high percentage of bullying accident done by the students in SMP Muhammadiyah Kudus does not mean hurt the friends physically and psychotically, but they only want to have fun with their friends. This finding is in line with Hamuddin, B etc (2019), that some students do bullying in order to have fun and make a joke with their friends.…”
Section: Findings and Discussionsupporting
confidence: 90%
“…The previous findings are consistent with those of Hamuddin et al (2019), which confirmed the three motives behind adolescents' practice of cyberbullying, amusement, response to abuse, and the expression of disturbing feelings. The findings of the Fluck (2017) study also confirmed that the motives of bullying are achieving goals, power, sadism, ideology, and revenge.…”
Section: Discussionsupporting
confidence: 85%
“…(Al-Enezi, 2021; Bussey & Fitzpatrick, 2014;George 2014;Kodama et al, 2016;Jung & Park, 2020;Nocera et al, 2022;Sharma, 2020). In cyberbullying, there are three common motives: amusement and entertainment, responding to abuse and bullying, and revenge (Hamuddin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Abrar (2014) states that a morphological process is a linguistic process that forms words. Within this process, people can create new words, use existing words in creative ways, and engage in linguistic wordplay (Hamuddin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%